Effect of initial stress on the reflection and transmission of plane waves at an imperfect interface between two orthotropic elastic half-spaces - Tung, D.X. (Archives of Mechanics, 2024)
The effects of initial stress on the reflection and transmission waves at the imperfect interface between two orthotropic half spaces are studied in this paper. A linear spring model is used to describe the imperfection of bonding behavior at the interface. Reflection and transmission coefficients (RTCs) have been derived analytically when a quasi-longitudinal (qP) wave strikes for both the imperfect and perfect interface. Finally, numerical examples are provided to show the effect of the imperfect interface, initial stress and incident angle on the RTCs, energy ratios, reflection and transmission angles of waves.